2018
DOI: 10.1140/epje/i2018-11643-6
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion-induced fingering instability in thin elastic films under strain

Abstract: In this study, thin elastic films supported on a rigid substrate are brought into contact with a spherical glass indenter. Upon contact, adhesive fingers emerge at the periphery of the contact patch with a characteristic wavelength. Elastic films are also pre-strained along one axis before the initiation of contact, causing the fingering pattern to become anisotropic and align with the axis along which the strain was applied. This transition from isotropic to anisotropic patterning is characterized quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…For adhesion-induced fingering instabilities, the wavelength is found to be independent of other parameters but only varies linearly with the film thickness, ,, that is, λ ∝ h , which is confirmed in our experiments (see Figure S6 in the Supporting Information for details). In the meanwhile, if there is no instability, the contact radius corresponding to pull-off force or zero contact force is (see the Supporting Information).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…For adhesion-induced fingering instabilities, the wavelength is found to be independent of other parameters but only varies linearly with the film thickness, ,, that is, λ ∝ h , which is confirmed in our experiments (see Figure S6 in the Supporting Information for details). In the meanwhile, if there is no instability, the contact radius corresponding to pull-off force or zero contact force is (see the Supporting Information).…”
Section: Resultssupporting
confidence: 83%
“…Adhesive contact of soft materials is becoming more and more important due to their numerous applications, including the fabrication of flexible electronics, , the design of soft robots, , the development of tough medical bandages, and the prevention of marine biofouling . In classical contact mechanics, when a spherical indenter contacts with a flat surface, a round contact region is implicitly assumed. , However, several recent experiments have shown that placing a large glass lens on ultrathin and soft films can induce fingering instability, that is, fingers emerge in the periphery of the contact region, which apparently violates the assumption of the round contact region. Although similar adhesion-related instabilities in other situations, such as the peeling front of sandwiched thin elastic films, the cavitation in the debonding of rigid punch, , the bulk instabilities when adhesion is so strong that the contact area is fixed, , and interfacial instability of thin films subjected to surface interactions, have been extensively explored theoretically and experimentally, main attention is paid to the pattern formation or morphology of the contact region .…”
Section: Introductionmentioning
confidence: 99%
“…Bilayer films were prepared on a biaxial straining apparatus shown schematically in fig. 2 and described previously [33,34]. The apparatus consisted of a 258 ± 2 µm thick Elastosil R sheet (Wacker Chemie AG), which is cut into a rounded "plus" shape, with a 1 cm diameter hole in the middle.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…51 On the nanoscale, however, viscous forces from water dominate, and macro-scale propulsion techniques are largely ineffective. 52 The solution to this problem is to incorporate an element of asymmetry into the nanoscale object, which is precisely what Wilson et al have done by expanding on the aforementioned work involving polymer stomatocytes. 53 Their approach, outlined in Figure 5, encapsulates platinum nanoparticles on the interior of stomatocytes, which act as a catalyst in the reduction of hydrogen peroxide.…”
Section: Polymersome Motilitymentioning
confidence: 99%